E-HEALTH BERBASIS MOBILE UNTUK MENINGKATKAN LAYANAN KLINIK - Andi Nurkholis; Eka Saputra (Universitas Teknokrat Indonesia, 2021)
E-health is a public service consisting of information and communication technology linked to all functional elements that serve the health sector as a knowledge base. Prospective patients must still fill out a registration form to complete the data at the Ngudi Waluyo Clinic, which results in long lines. Furthermore, information about outpatient registration procedures and practicing doctors is difficult to access, and patient medical records are still written in notebooks traditionally. As a result, searching for patient history data will take a long time, and there is no backup of these records, which can cause data loss at any time. This study aims to develop mobile-based e-health to improve clinical services and make it easier for the public to obtain health services. The system was developed using the extreme programming method applied in mobile applications by utilizing PHP as programming language and MySQL as a database and system testing using the ISO 25010 standard. Through e-health, patients can register outpatients anytime and anywhere without queue, improving the quality of service at the Ngudi Waluyo clinic. Based on the testing results on ten respondents, it was found that the developed e-health was feasible to use with a final score of 90.59%.